FRI0373 ASSOCIATIONS OF VASCULAR PATHOPHYSIOLOGY AND BONE METABOLISM IN ANTI-TNF- TREATED RHEUMATOID ARTHRITIS AND ANKYLOSING SPONDYLITIS PATIENTS. (13th June 2020) - Czókolyová, M.; Gulyás, K.; Horváth, Á.; Végh, E.; Pethö, Z.; Szamosi, S.; Hamar, A.; Pusztai, A.; Balogh, E.; Bodnár, N.; Bodoki, L.; Szentpetery, A.; et al.
Abstract : Background: Cardiovascular (CV) disease and osteoporosis (OP) have become increasing challenges in the ageing population, even more in patients with inflammatory rheumatic diseases, such as rheumatoid arthritis (RA) and spondyloarthropathies. Both RA and ankylosing spondylitis (AS) have been associated with generalized and localized bone loss, accelerated atherosclerosis, increased CV morbidity and mortality. Objectives: Bone and vascular biomarkers and parameters along with the effect of one-year anti-TNF therapy on these markers were assessed in order to determine correlations between vascular pathophysiology and bone metabolism in RA and AS. Methods: Fifty-three patients including 36 RA patients treated with etanercept (ETN) or certolizumab pegol (CZP) and 17 AS patients treated with ETN were included in a 12-month follow-up study. Bone and vascular markers were assessed by ELISA. Bone density was assessed by DXA and quantitative CT (QCT). Flow-mediated vasodilation (FMD), common carotid intima-media thickness (ccIMT) and pulse-wave velocity (PWV) were assessed by ultrasound. The effects of vascular markers on bone and bone effects on vasculature undergone statistical analysis. Results: Serum levels of vascular endothelial growth factor (VEGF), PDGF-BB, angiopoietin 2 (Ang2) and cathepsin K (CathK) decreased, procollagen type 1 N-propeptide (P1NP) and sclerostin (SOST) levels increased, soluble receptor activator nuclear kappa B ligand (sRANKL) and osteoprotegerin (OPG) levels showed no differences. When bone and vascular markers were correlated with each other, at baseline, OPG correlated with Ang2 and adiponectin. SOST correlated positively with ccIMT. DXA L2-4 BMD, DXA L1 BMD and DXA femoral neck (FN) BMD correlated with FMD and CRP. QCT trabecular BMD correlated with ccIMT and PON1. According to the univariate analysis, FMD correlated with OPG, ccIMT correlated with SOST and QCT trabecular BMD. Ang1, Ang2 and PDGF-BB showed correlation with Dickkopf-1 (DKK1). Ang2 also correlated with OPG. As suggested by the multivariate analysis, OPG determined FMD; DKK1 was an independent predictor of Ang1, Ang2 and PDGF-BB. OPG was a predictor of Ang2. Conclusion: In our study of anti-TNF treated RA and AS patients, vascular and bone parameters showed numerous correlations. The therapy was clinically effective, it halted further bone loss over 1 year and reduced the production of angiogenic markers. Acknowledgments: This research was supported by an investigator-initiated research grant from Pfizer. Disclosure of Interests: Monika Czókolyová: None declared, Katalin Gulyás: None declared, Ágnes Horváth: None declared, Edit Végh: None declared, Zsófia Pethö: None declared, Szilvia Szamosi: None declared, Attila Hamar: None declared, Anita Pusztai: None declared, Emese Balogh: None declared, Nóra Bodnár: None declared, Levente Bodoki: None declared, Agnes Szentpetery: None declared, Harjit Pal Bhattoa: None declared, György Kerekes: None declared, Katalin Hodosi: None declared, Andrea Domjan: None declared, Sándor Szántó: None declared, Gabriella Szücs: None declared, Hennie Raterman Grant/research support from: UCB, Consultant of: Abbvie, Amgen, Bristol-Myers Sqibb, Cellgene and Sanofi Genzyme, WIllem Lems Grant/research support from: Pfizer, Consultant of: Lilly, Pfizer, Zoltán Szekanecz Grant/research support from: Pfizer, UCB, Consultant of: Sanofi, MSD, Abbvie, Pfizer, Roche, Novertis, Lilly, Gedeon Richter, Amgen